Pemanfaatan Sampah Anorganik Sebagai Produk Ecobrick dalam Menanggulangi Sampah di Desa Ketimang - Ramadhany Hananto Puriana; Dinda Mayang Adella Putri; Reza Sastra Maharani; Dio Maulana Nursyam; Khoirun Nisa; Nabila Rahma Lubis (Jurnal Pengabdian Masyarakat (abdira), 2022)
The problem of waste, especially inorganic waste is a problem that is still crucial in society. The increasing population every year results in an increase in the volume of waste. Lack of socialization regarding the utilization and utilization of waste has a negative impact on the environment and public health. Ecobrick is a waste management activity, especially inorganic waste by putting inorganic waste into plastic bottles. This service activity was carried out in Ketimang Village, Wonoayu District, Sidoarjo Regency. The goal is to educate the people of Ketimang Village about how to manage plastic waste so that it can reduce the amount of daily waste in the Ketimang Village environment. The method used is the socialization of organic and inorganic waste and waste management into Ecobrick. This Ecobrick activity produces a product, namely flower pots from inorganic waste. The response of the community, especially the youth organizations who were participants in the activity, was very enthusiastic during the implementation of the Ecobrick activity.